2021
DOI: 10.1038/s41598-021-88988-w
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-mediated DNA damage response is synthetic lethal with G-quadruplex stabilizer CX-5461

Abstract: CX-5461 is a G-quadruplex (G4) ligand currently in trials with initial indications of clinical activity in cancers with defects in homologous recombination repair. To identify more genetic defects that could sensitize tumors to CX-5461, we tested synthetic lethality for 480 DNA repair and genome maintenance genes to CX-5461, pyridostatin (PDS), a structurally unrelated G4-specific stabilizer, and BMH-21, which binds GC-rich DNA but not G4 structures. We identified multiple members of HRD, Fanconi Anemia pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…11 , 13 ). Recently, it has been shown that RNF168, which promotes the recruitment of the RAD18-SLF1/2-SMC5/6 pathway to damaged replication forks, is important for signaling the presence of G-quadruplex (G4) DNA structures stabilized by the RNA polymerase I inhibitor, CX5461 47 . Since cells deficient in BRCA1/2 and the cohesin-associated helicase DDX11 are also hypersensitive to this agent 48 , 49 and DDX11 was shown to function with SMC5/6 to repair DNA damage 17 , 50 , 51 , we hypothesized that the RAD18-SLF1/2-SMC5/6 pathway might play a role in suppressing replication stress at sites of stabilized G4 structures.…”
Section: Resultsmentioning
confidence: 99%
“…11 , 13 ). Recently, it has been shown that RNF168, which promotes the recruitment of the RAD18-SLF1/2-SMC5/6 pathway to damaged replication forks, is important for signaling the presence of G-quadruplex (G4) DNA structures stabilized by the RNA polymerase I inhibitor, CX5461 47 . Since cells deficient in BRCA1/2 and the cohesin-associated helicase DDX11 are also hypersensitive to this agent 48 , 49 and DDX11 was shown to function with SMC5/6 to repair DNA damage 17 , 50 , 51 , we hypothesized that the RAD18-SLF1/2-SMC5/6 pathway might play a role in suppressing replication stress at sites of stabilized G4 structures.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, RNF168 deficiency leads to the resistance of TOP2α catalytic inhibitor ICRF-193 and the cytotoxic anticancer drug etoposide (VP-16) [ 44 ]. Moreover, deletion of RNF168 inhibits the chromatin ubiquitin pathway and enhances the sensitivity of cancer cells to the bioavailable derivative of quarfloxin CX-5461 [ 45 ]. A recent study showed that a 1,2,3-triazole derivative of quinazoline can directly bind with autophagy-related protein SQSTM1/P62 and E3 ligase RNF168, promote their interaction, and damage the DNA repair mediated by RNF168, thus increasing the sensitivity of colon cancer cell HCT-116 to X-ray radiation.…”
Section: Structure and Functions Of Rnf168mentioning
confidence: 99%
“…CX-5461 is another G4 ligand that is currently at advanced phase I clinical trials for patients with BRCA1/2 deficient tumors [ 69 ]. Recently, Masud et al demonstrated that inhibition of the critical member of the DNA damage response, UBE2N , acted synergistically with CX-5461 increasing cell toxicity [ 70 ]. Further, this compound has shown the potential to suppress pulmonary arterial hypertension and associated vascular remodeling and pulmonary inflammation by inhibiting the RNA polymerase I [ 71 ].…”
Section: Overview Of G4-interacting Ligandsmentioning
confidence: 99%